Relationship between DMFT index and reproductive history- a cross-sectional study on enrollment phase of Azar cohort study - Sahra Hefzollesan; Nasrin Sharififard; Zeinab Mahboobi; Elnaz Faramarzi (BMC, 2022)
Abstract Background Hormonal changes in women throughout life might affect the oral health. The aim of this study is to investigate the relationship between the Decayed, Missing, and Filled Teeth (DMFT) index and reproductive history. Methods The present cross-sectional study was performed using data of Azar Cohort Study conducted in 2014, in Shabestar city, East Azerbaijan Province, Iran. In the present study, the data of all 8294 women from the enrollment phase of the Azar cohort were included. All available data related on the variables of reproductive history (including age at the onset of menstruation, age of onset of menopause, age of first pregnancy, and frequency of pregnancy), age at interview, educational level, socioeconomic status, frequency of tooth brushing, chronic diseases, body mass index and DMFT were extracted. Negative binomial regression with loglink was used to analyze the relationship between variables. Three regression models have been applied to adjust the effect of confounding variables. Model 1 adjusted for education, socio-economic status, age, chronic diseases, body mass index and frequency of tooth brushing. Model 2 adjusted for education, socioeconomic status, age, chronic diseases and body mass index. Model 3 adjusted for education, socio-economic status and age. Results The mean DMFT of 8294 women was 20.99 ± 8.95. In model 1, there was no significant relationship between DMFT and frequency of pregnancy. However, model 2 and 3 showed that in women who had four or more pregnancies, the DMFT rate was significantly higher than those who did not have a history of pregnancy (P = 0.02, P = 0.04). Age at the onset of menopause, age at the onset of menstruation and age of first pregnancy had no significant relationship with DMFT in the models. Brushing less than once a day and increasing age at interview had significant relationship with DMFT in the models (P < 0.001). Conclusion Despite hormonal changes through the life, the history of reproductive showed no significant relationship with women's DMFT. Oral health education for women is an important step in promoting oral health and it is necessary to pay special attention to preventive programs in oral health policy for women specially with increasing the age.